Recommendations for the clinical use of somatosensory-evoked potentials - Cruccu, G.; Aminoff, M.J.; Curio, G.; Guerit, J.M.; Kakigi, R.; Mauguiere, F.; Rossini, P.M.; Treede, R.-D.; Garcia-Larrea, L. (Clinical neurophysiology, 2008)
The International Federation of Clinical Neurophysiology (IFCN) is in the process of updating its Recommendations for clinical practice published in 1999. These new recommendations dedicated to somatosensory-evoked potentials (SEPs) update the methodological aspects and general clinical applications of standard SEPs, and introduce new sections dedicated to the anatomical–functional organization of the somatosensory system and to special clinical applications, such as intraoperative monitoring, recordings in the intensive care unit, pain-related evoked potentials, and trigeminal and pudendal SEPs. Standard SEPs have gained an established role in the health system, and the special clinical applications we describe here are drawing increasing interest. However, to prove clinically useful each of them requires a dedicated knowledge, both technical and pathophysiological. In this article we give technical advice, report normative values, and discuss clinical applications.